Serum Magnesium Level in Hospitalized Nephrotic Syndrome Patients and Its Relation to Cholesterol - Chaudhury, Gulshan Nigar; Hanif, Mohammad (BIRDEM Medical Journal, 2017)
Background: Nephrotic syndrome (NS) is a common childhood renal disease all over the world. This study was designed to evaluate the magnesium level in patients with nephrotic syndrome and its relation to cholesterol. Methods: An observational cross sectional study was conducted in the Department of Pediatrics, Dhaka Shishu Hospital, Dhaka from January 2015 to June 2015. Fifty four diagnosed cases of nephrotic syndrome admitted during the study period in this hospital were included in this study and patients of NS with associated illnesses such as diarrhoea, severe vomiting and already have metabolic disturbances and seizure were excluded in this study. Serum magnesium and cholesterol levels were assessed in every enrolled patients. Results: The mean level of serum magnesium during initial attack was 2.28±0.36, and it was 2.04±0.29 during first relapse, 2.06±0.29 during infrequent relapse and 1.76±0.32 during frequent relapse. The difference found among the mean level of serum magnesium level in different pattern of nephrotic syndrome by ANOVA test (one way) was statistically significant (P <0.01). All the patients had severely high cholesterol level and about 22% of them had mg level at <1.8 mg/dl, 52% of them had mg level at 1.8-2.4 mg/dl and 26% of them had mg level >2.4 mg/dl. The p value is 0.1 which signifies statistically insignificant correlation between the mg level and cholesterol level. Inverse correlation with serum magnesium with serum cholesterol in children with nephrotic syndrome and that was statistically not significant (r = -0.179, p = 0.1). Conclusion: Serum magnesium level is low in most(64.3%) cases of frequent relapse nephrotic syndrome. Inverse correlation with serum magnesium with serum cholesterol in children with nephrotic syndrome and that was statistically not significant. Birdem Med J 2017; 7(1): 12-16